2016
DOI: 10.1051/matecconf/20164705018
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nitrogen Co-Doped P25: Parameter Study on Photodegradation of Reactive Red 4

Abstract: Abstract. Photocatalytic degradation rate of reactive red 4 (RR4) using carbon coated nitrogen doped TiO2 (C N co-doped TiO2) in photocatalysis process is main goal on this research. The main operating the parameters such as effect of initial dye concentration, catalyst loading, aeration flow rate and initial pH on degradation of RR4 under 45 W fluorescent lamp was investigated. photocatalytic activity of RR4 dye decreased with increasing RR4 dye concentration. The optimum loading is around 0.04 g and optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…This was proven by Trevisan and co-workers who also observed that the carbonate species with binding energies of ∼289 eV could incorporate some of the lattice Ti atoms and form a Ti–O–C structure . Azami and co-workers also discovered that the doped C could form a layer on the surface of TiO 2 NPs with a mixture of C and carbonate species . This is known as the interstitial site of the TiO 2 lattice by C atoms, which is in good agreement with the XRD finding, where it can increase the absorption of visible light by TiO 2 during photocatalytic reactions.…”
Section: Resultssupporting
confidence: 69%
“…This was proven by Trevisan and co-workers who also observed that the carbonate species with binding energies of ∼289 eV could incorporate some of the lattice Ti atoms and form a Ti–O–C structure . Azami and co-workers also discovered that the doped C could form a layer on the surface of TiO 2 NPs with a mixture of C and carbonate species . This is known as the interstitial site of the TiO 2 lattice by C atoms, which is in good agreement with the XRD finding, where it can increase the absorption of visible light by TiO 2 during photocatalytic reactions.…”
Section: Resultssupporting
confidence: 69%
“…The sol-gel method is the most flexible method of doping TiO2 at room temperature. The characteristics of the final product could be easily controlled depending on the reaction conditions such as solvents, pH, and temperature, as well as calcination conditions (Lin et al, 2011;Iwase et al, 2013;Lin et al, 2013;Han et al, 2014;Azami et al, 2016;Bakar and Ribeiro, 2016a;Giannakas et al, 2016). The sol-gel preparation process is rather a more time-consuming method than an energy-consuming method (Figure 6.5).…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…In the microwave reactor, the solution can be heated above its boiling point by electromagnetic radiation in a closed system, and the reactor can withstand the high pressure created from the doping process (Figure 6.7). Hence, the reaction time would be greatly shortened (Azami et al, 2016).…”
Section: Microwave-assisted Methodsmentioning
confidence: 99%
“…The increasing amount of catalyst produces the number of sites available for photons absorption thus more hydroxyl radical (•OH) is formed to degrade the organic molecule of violet-3B dye [27][28]. However, the addition of C-N-codoped TiO 2 dosage higher than 0.3 g L -1 caused the decrease in removal percentage of violet-3B dye to 71%.…”
Section: Effect Of Catalyst Dosagementioning
confidence: 99%
“…By increasing the initial concentration of dye lead to a decrease in violet-3B degradation rate. This effect can be explained by the increase in the dye concentration, caused the decrease in the light penetration that reaches the organic molecule of violet-3B dye due to the declining transparency of the solution into a more concentrated solution [27][28]. Thus, the time for complete degradation of violet-3B dye would be longer for higher initial violet-3B concentrations [29,32].…”
Section: Effect Of Initial Dye Concentrationmentioning
confidence: 99%